Multifunctionality of Agriculture – Conceptualisation and Operationalisation of the Phenomenon - Wilkin, Jerzy (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2009)
The article deals with one of the most important questions concerning agriculture and agricultural policy at present, namely the question of agriculture’s multifunctionality and the phenomenon’s relation to agricultural policy, especially at the EU level. The article marks an attempt at the identification of agriculture’s function in relation to market production and non-market production as well as its influence on the natural environment and on the social and cultural spheres. The author analyses the phenomenon of agriculture’s mutifunctionality in the context of the concept of sustainable development, the problem of evaluation of the non-market functions of agriculture, the problem of food safety and legitimisation of public assistance to agriculture in the European Union.
Keywords: multifunctionality of agriculture; common agricultural policy; European model of agriculture; agricultural economics